2005
DOI: 10.1007/s00299-005-0936-x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of in vitro-grown shoot tips of raspberry (Rubus idaeus L.) by encapsulation–vitrification and encapsulation–dehydration

Abstract: The first efficient cryopreservation procedure for in vitro-grown shoot tips of raspberry (Rubus idaeus L.) has been developed based on encapsulation-vitrification (EnVi) and encapsulation-dehydration (EnDe). EnVi resulted in higher survival (85%) and regrowth (75%) of cryopreserved shoot tips than EnDe (65 and 50%, respectively). In both cryogenic procedures, shoots regenerated from cryopreserved shoot tips without intermediary callus formation. Histological studies showed that a much larger number of meriste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 19 publications
1
52
1
4
Order By: Relevance
“…Furthermore, DAB has recently applied cryotherapy as a novel means for eradication of viruses and phytoplasma from vegetatively propagated plants, which results in virusfree plants with a much higher frequency than the previously used methods . At the same time, Laukaa Research and Elite Plant Unit of MTT has developed cryopreservation techniques for perennial horticultural plants (Wang et al 2005) and in collaboration with DAB introduced the cryotherapy technique to healthy plant production. Consequently, Finland has become a forerunner in the use of this approach.…”
Section: Potato Biotechnologymentioning
confidence: 99%
“…Furthermore, DAB has recently applied cryotherapy as a novel means for eradication of viruses and phytoplasma from vegetatively propagated plants, which results in virusfree plants with a much higher frequency than the previously used methods . At the same time, Laukaa Research and Elite Plant Unit of MTT has developed cryopreservation techniques for perennial horticultural plants (Wang et al 2005) and in collaboration with DAB introduced the cryotherapy technique to healthy plant production. Consequently, Finland has become a forerunner in the use of this approach.…”
Section: Potato Biotechnologymentioning
confidence: 99%
“…These authors found that only the shoot apices with water content lower than 22.5% survived. Wang, Laamanen, Uosukainen, & Valkonen (2005) observed that sodium alginate capsules containing apical buds of Rubus idaeus L., pre-cultured in MS medium containing sucrose, had an initial moisture content of 66%, and the water content decreased to 22.2% in the first 4 hours in an airflow hood, and to 14.3% after 8 hours of dehydration. According to these authors, the highest recovery rates of the apical buds were obtained by dehydration for at least 3 hours in an airflow hood.…”
Section: Encapsulation-dehydrationmentioning
confidence: 99%
“…A este respecto, se han probado técnicas como la organogénesis directa e indirecta utilizando hojas de diferentes variedades comerciales (Isac, 2009) y la criopreservación de brotes apicales (Wang et al, 2005;Gupta y Reed, 2006). Algunos sistemas para la micropropagación de frambuesa han utilizadoel medio de cultivo MS (Muashige y Skoog, 1692) semisólido y líquido en inmersión temporal complementado con bencil amino purina (BAP), ácido giberélico (AG 3 ) y ácido ascórbico (Jones y Flores, 2007); también se reporta el uso de N 6 -benciladenina, tidiazuron y zeatina (Reed, 1991;Popescue Isac, 1999;González et al, 2000;Vujović et al, 2009).…”
Section: Introductionunclassified
“…In this regard, techniques like direct and indirect organogenesis have been used, using leaves from different commercial varieties (Isac, 2009) and cryopreservation of apical shoots (Wang et al, 2005;Gupta and Reed, 2006). Some systems for raspberry micro propagation have used MS medium (Muashige and Skoog, 1692) semisolid and liquid in temporary immersion supplemented with benzyl amino purine (BAP), gibberellic acid (GA 3 ) and ascorbic acid (Jones and Flores, 2007); the use of N 6 -benzyladenine, thidiazuron and zeatin (Reed, 1991;Popescue Isac, 1999;González et al, 2000;Vujović et al, 2009) has also been reported.…”
Section: Introductionmentioning
confidence: 99%